Cigarette smoking, systolic blood pressure, and cardiovascular diseases in the asia-pacific region - Nakamura, K.; Barzi, F.; Lam, T.; Huxley, Rachel; Feigin, V.; Ueshima, H.; Woo, J.; Gu, D.; Ohkubo, T.; Lawes, C.; Suh, I.; Woodward, M. (Lippincott Williams & Wilkins, 2008)
BACKGROUND AND PURPOSE: Smoking and increased levels of blood pressure (BP) substantially increase the risk of cardiovascular diseases (CVD). If these 2 risk factors have a synergistic impact on cardiovascular events, lowering BP and quitting smoking will contribute more to reducing CVD than would be expected from ignoring their interaction. METHODS: Individual participant data were combined from 41 cohorts, involving 563 144 participants (82% Asian). During a median of 6.8 years follow-up, 4344 coronary heart disease (CHD) and 5906 stroke events were recorded. Repeat measures of systolic blood pressure (SBP) were used to adjust for regression dilution bias. Hazard ratios (HRs) and 95% confidence intervals (CIs) for SBP by cigarette smoking status were estimated from Cox proportional hazard models adjusted for age and stratified by study and sex. RESULTS: Data suggested a log-linear relationship between SBP and all subtypes of CVD. The HRs relating SBP to both CHD and ischemic stroke were broadly similar irrespective of smoking status (Pg‰¥0.1). For hemorrhagic stroke (intracerebral hemorrhage), the HRs (95% CIs) for an additional 10 mm Hg increment in SBP were 1.81 (1.73 to 1.90) for present smokers and 1.66 (1.59 to 1.73) for nonsmokers (P=0.003). For every subtype of cardiovascular events, similar results were found for analyses involving only fatal events. CONCLUSIONS: Smoking exacerbated the impact of SBP on the risk of hemorrhagic stroke. Although quitting smoking and lowering BP are both crucial for prevention of CVD, combining the 2 could be expected to have extra beneficial effect on preventing hemorrhagic stroke. © 2008 American Heart Association, Inc.